Analisis Perbandingan Fasilitas Aplikasi Mobile Banking Bank Syariah Mandiri KCP. Bengkalis Dengan Bank Mandiri KC. Bengkalis - Miftahuddin, Miftahuddin; Hendarsyah, Decky (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
Mobile Banking is a banking service using mobile communication tools such as mobile phones by providing many facilities for banking transactions through applications on mobile phones. This research was conducted to find out the Comparison of Bank Syariah Mandiri Bengkalis Branch Office Mobile Banking Application Facilities with Bank Mandiri Bengkalis Branch Office. The research method used in this study is a qualitative descriptive method by comparing the facilities, rates, number of user customers and the security of the Mobile Banking of both banks, then how to use Mobile Banking from an Islamic perspective. After being investigated, it was found that Bank Mandiri Mobile Banking application facilities were better than Bank Syariah Mandiri. Whereas Mobile Banking in an Islamic perspective may be done because it does not cause harm but it is something that brings many benefits.